2010
DOI: 10.1016/j.bbr.2009.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Naming facilitation induced by transcranial direct current stimulation

Abstract: Transcranial direct current stimulation (tDCS) is able to generate a long-term increase or decrease in the neuronal excitability that can modulate cognitive tasks, similar to repetitive transcranial magnetic stimulation. The aim of this study was to explore the effects of tDCS on a language task in young healthy subjects. Anodal, cathodal and sham tDCS were applied to the left dorsolateral prefrontal cortex (DLPFC) before two picture naming experiments, a preliminary study (i.e., experiment 1) and a main study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
180
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(193 citation statements)
references
References 46 publications
9
180
2
2
Order By: Relevance
“…After the FORCEtraining with tDCS with the anode placed over M1, using a questionnaire developed by Brunoni et al (2011) andFertonani et al (2010), we asked participants to report the presence and severity (none-mild-moderate-considerable-strong) of feelings of itchiness, tingling, headache, neck pain, scalp pain, burning, warmth/heat, pinching, iron taste, fatigue, concentration difficulties and acute mood changes. In addition, the start (beginning, middle or end of stimulation) and duration (stopped soon, in the middle or towards the end of the stimulation) of these sensations was questioned and participants were asked if the sensations influenced their performance (not at all, a little, considerably, much, very much).…”
Section: Questionnairesmentioning
confidence: 99%
“…After the FORCEtraining with tDCS with the anode placed over M1, using a questionnaire developed by Brunoni et al (2011) andFertonani et al (2010), we asked participants to report the presence and severity (none-mild-moderate-considerable-strong) of feelings of itchiness, tingling, headache, neck pain, scalp pain, burning, warmth/heat, pinching, iron taste, fatigue, concentration difficulties and acute mood changes. In addition, the start (beginning, middle or end of stimulation) and duration (stopped soon, in the middle or towards the end of the stimulation) of these sensations was questioned and participants were asked if the sensations influenced their performance (not at all, a little, considerably, much, very much).…”
Section: Questionnairesmentioning
confidence: 99%
“…At the end of both stimulation sessions, participants completed a tDCS sensation rating scale, which asked them to rate the duration of sensations and the intensity of itchiness, pain, burning, heat, pinching, iron taste and fatigue (adapted from Fertonani, Rosini, Cotelli, Rossini, & Miniussi, 2010). Responses showed that tDCS was well-tolerated and ratings of sensations confirmed that participants could not reliably distinguish when they had been receiving sham or active stimulation (no differences for any of the sensations, Table 2).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…As per Fertonani et al (2010), sensation intensities were rated on the following 5-point scale: 0=none, 1=mild, 2=moderate, 3=considerable, 4=strong. Two-tailed p values were obtained with Wilcoxon matched pairs tests.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…At the end of each tDCS stimulation, the participants completed a questionnaire about sensations experienced during the two stimulations (anodal vs. cathodal) to evaluate whether the tDCS caused any discomfort (Fertonani et al, 2010).…”
Section: Sensations Induced By Tdcsmentioning
confidence: 99%